Effects of Indole-3-Acetic Acid and Kinetin on the Adenosine Deaminase Activity in Various Tissues of Rats - Tuluce, Yasin; Celik, Ismail (Asian Journal of Chemistry, 2010)
The effects of a sub-lethal concentration of some plant growth regulators on heart, kidney and muscle adenosine deaminase activity in female rats (Sprague-Dawley) were investigated under laboratory conditions. Thirty-six Sprague-Dawley albino rats were divided into three experimental groups: control and plant growrh regulator treatment [indole-3-acetic acid and kinetin]. 100 ppm each of plant growrh regulators, indole-3-acetic acid and kinetin were administered orally to 12 rats ad libitum for 25 d continuously. The hormone treatment caused different effects on the heart adenosine deaminase activity in comparison to those of the control rats. According to results, while the heart adenosine deaminase activity was decreased significantly by indole-3-acetic acid and kinetin, these plant growrh regulators did not affect the adenosine deaminase activity of kidney and muscle tissues. In conclusion, these chemicals have toxicological effects on the animals in subacute treatment.